2008
DOI: 10.1111/j.1540-8183.2008.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus‐ and Zotarolimus‐Eluting Stents for Bare Metal Stent In‐Stent Restenosis Treatment: A Prospective Study

Abstract: In this prospective study, we showed that direct nDES implantation is highly effective for ISR and seems to be a promising management for the treatment of ISR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The safety endpoint comprised a composite of allcause death and non-fatal myocardial infarction. Major adverse cardiac events, a composite of cardiac death, non-fatal myocardial infarction and target vessel revascularisation was considered for the purposes of increased comparability with previous studies [2,15,20]. To prevent double counting of individual end-points within the composite endpoints a hierarchical count of endpoints was utilised such that death took priority over MI over TVR over angina.…”
Section: Study Endpoints and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety endpoint comprised a composite of allcause death and non-fatal myocardial infarction. Major adverse cardiac events, a composite of cardiac death, non-fatal myocardial infarction and target vessel revascularisation was considered for the purposes of increased comparability with previous studies [2,15,20]. To prevent double counting of individual end-points within the composite endpoints a hierarchical count of endpoints was utilised such that death took priority over MI over TVR over angina.…”
Section: Study Endpoints and Definitionsmentioning
confidence: 99%
“…More limited data exist regarding the efficacy of secondgeneration DES in the treatment of either BMS or DES ISR, despite the widespread use of both stent types in ISR treatment. Current evidence has been limited to a prospective study directly comparing ZES and EES [15] with limited sample sizes and no comparison to first-generation DES. A larger non-randomised study compared EES to PES in BMS ISR only and found reduced adverse event rates at one year in the EES group, and no difference in rates at long-term follow-up [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this finding, their implantation has become increasingly common over the recent years and a majority of > 2 million patients are taking at least one type of these novel stents [56]. Although new types of DESs have been developing [57], however, SESs and PESs have been implanted more than the others and most of the published RCTs have utilized the two thus far [1,2,4,6,7,[12][13][14][15][16][17][18][19][42][43][44][45][46][47][48][49][50][51][52][53][54]. Notwithstanding the agreement of several studies with dramatic restenosis benefits of SESs [1,43,45,46] and PESs 2-4,7,50,51,54] compared with BMSs, there are considerable discrepancies among RCTs, [1,2,4,6,7,[12][13][14][15][16][17][18][19][42]…”
Section: Fig 10 Meta-analysis Of Stent Thrombosismentioning
confidence: 99%